A survey on different types of generalized recurrency on the weyl manifold - Baştan, Füsun Nurcan (Marmara Üniversitesi Fen Bilimleri Dergisi, 2013)
Hayden [1] introduced a semi symmetric metric connection on the Rie-mannian manifolds. This definition was developed by Yano [2] and Imai [3-4]. In [5], we examined the Weyl manifold, which is the generalization of the Riemannian manifold, admitting a semi symmetric connection. Pavel Enghish [6-7] examined the recurrency and generalized recurrency on the Riemannian manifolds with respect to symmetric and semi symmetric connections. The aim of this paper is to obtain the relations between different types of the Weyl manifolds under some special conditions which are concerning the definitions of generalized recurrency, generalized conformally recurrency and generalized projectively recurrency.
Keywords: Weyl manifold; semi symmetric connection; conformal curvature tensor; projective curvature tensor; generalized recurrency